Wikipedia as a cultural lens: a quantitative approach for exploring cultural networks - Luis A. Miccio; Paschalis Agapitos; Carlos Gamez-Perez; Francisco González; Juan Luis Suarez; Gustavo A. Schwartz (Humanities & Social Sciences Communications)
Abstract The structure of cultural networks emerges from complex interactions among many elements related to people, ideas, and objects. However, these interactions can be very subtle and difficult to quantify, precluding a quantitative analysis of the cultural networks that can be crucial to understanding complex dynamics better. In this work, we propose a new approach that combines the formalism of complex networks, the structural relationship between nodes, and the corpus of Wikipedia to map and analyse the interactions among cultural entities. To test the proposed methodology, we study the case of the interdisciplinary cultural network connecting art, science, and philosophy in Europe in the seventeenth century. The results are aligned with well-established historical knowledge of the period and, more importantly, provide new insights to unveil how elements in these networks interact with each other. In particular, we found that nodes within a given cluster, related respectively to art, science or philosophy, interact with nodes in the same cluster following a core-periphery behaviour. In contrast, inter-cluster interactions across disciplines follow a power law distribution.